2014
DOI: 10.1146/annurev-genet-120213-092509
|View full text |Cite
|
Sign up to set email alerts
|

Factors Underlying Restricted Crossover Localization in Barley Meiosis

Abstract: Meiotic recombination results in the formation of cytological structures known as chiasmata at the sites of genetic crossovers (COs). The formation of at least one chiasma/CO between homologous chromosome pairs is essential for accurate chromosome segregation at the first meiotic division as well as for generating genetic variation. Although DNA double-strand breaks, which initiate recombination, are widely distributed along the chromosomes, this is not necessarily reflected in the chiasma distribution. In man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 98 publications
(89 reference statements)
4
63
0
Order By: Relevance
“…Nonetheless, the initiation of SC formation in subtelomeric regions at the bouquet stage and the early localization of recombination proteins to these regions also have been seen in barley (62,63). However, as zygotene proceeds, numerous medial sites of SC initiation are observed also.…”
Section: Discussionmentioning
confidence: 92%
“…Nonetheless, the initiation of SC formation in subtelomeric regions at the bouquet stage and the early localization of recombination proteins to these regions also have been seen in barley (62,63). However, as zygotene proceeds, numerous medial sites of SC initiation are observed also.…”
Section: Discussionmentioning
confidence: 92%
“…The two distal regions were characterized by an elevated meiotic recombination rate (of 0.60 and 0.96 cM/Mb) which was clearly distinct from the low meiotic recombination rate (of 0.05 cM/Mb) observed in the large proximal region spanning the centromeric-pericentromeric area [115]. Different studies are underway to understand the mechanisms (and the genes) regulating the formation of crossovers to allow the control of their frequency and position [116]. For example, it was shown that a mutation of the Arabidopsis FANCM gene results in a substantial increase of meiotic crossover formation, without negative impacts on chromosome stability [117].…”
Section: The Control Of Genetic Recombinationmentioning
confidence: 97%
“…Understanding meiotic recombination will be important as it has a significant influence on genetic diversity and speciation, for example, axis proteins have been implicated in the evolution of polyploid Arabidopsis species [137,138]. In addition, knowledge of how crossovers are controlled will allow this process to be manipulated in useful ways in crop species [6].…”
Section: Prospectsmentioning
confidence: 99%
“…The precise advantage that sexual reproduction confers is debated, though its advantages must be strong and general as it is maintained in unicellular and multicellular species of variable population sizes and ecologies [4,5]. It is also important to understand meiotic recombination in the context of agricultural breeding, where homologous recombination can be restricted to specific chromosomal regions and thereby limit use of crop genetic variability [6].…”
mentioning
confidence: 99%